Influência de níveis de tensão de água no solo sobre o desenvolvimento do feijoeiro-comum - Scarpi, Maria Cecilia Fonseca (2016)
The water availability is one of the main factors that reduce the productivity of common bean, a crop of great national socioeconomic importance, which emphasizes the importance of irrigation management in order to guarantee the supply and maintenance of